Student Presentations Upgrades Through Use of Language Learning Strategies - Iis Lisnawati; Yuyun Yuniawati; Titin Kusmini (JETL (Journal of Education, Teaching and Learning), 2017)
This research is experimental testing of Language Learning Strategies to improve student presentation at the Indonesian Department of Education, University of Siliwangi Tasikmalaya. Learning stage presentations using Language Learning Strategies are as follows. (1) preparation, (2) presentation, (3) practice, (4) evaluation, (5) expansion activities. In each stage been LLS is eclectic in accordance with the needs of learning, good learning objectives, material characteristics, and the characteristics of the students. There is a significant difference between the mean score of the pretest to posttest mean score in the experimental class and there is a significant difference between the mean score of posttest in the experimental class with a mean score of posttest in control classes. This proves that effective language learning strategies to improve student presentation.